Effect of a High‐Fat Meal on the Pharmacokinetics of the HIV Integrase Inhibitor Cabotegravir. Issue 4 (19th September 2018) - Patel, Parul; Ford, Susan L.; Lou, Yu; Bakshi, Kalpana; Tenorio, Allan R.; Zhang, Zhiping; Pan, Rennan; Spreen, William
Abstract: Cabotegravir is an integrase inhibitor in clinical development for the treatment and prevention of HIV infection using oral tablets for short‐term, lead‐in use before subsequent administration of a long‐acting injectable formulation. This phase 1, single‐center, randomized, 2 × 2 crossover study evaluated the effect of a high‐fat meal on the pharmacokinetics (PK) of oral cabotegravir. Healthy adults received oral cabotegravir 30 mg as a single dose on 2 separate occasions, either after fasting or following a high‐fat meal (∼53% fat, ∼870 kcal). Safety evaluations and serial PK samples were collected, and a mixed‐effects model was used to determine within‐participant treatment comparison of noncompartmental PK parameters. Twenty‐four patients were enrolled and had a mean body mass index of 25.6 kg/m 2 ; 67% were male. Compared with the fasting state, coadministration of cabotegravir with a high‐fat meal increased plasma cabotegravir area under the concentration‐time curve and maximal drug concentration, each by 14%. The slight 14% to 17% increase in exposure associated with a high‐fat, high‐calorie meal was not considered clinically significant. No grade 3/4 adverse events (AEs), drug‐related AEs, or AEs leading to discontinuation were reported.